2010
DOI: 10.1002/bem.20605
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation studies of Soviet research on immunological effects of microwaves: Russian immunology results

Abstract: This paper presents the results of a replication study performed to investigate earlier Soviet studies conducted between 1974 and 1991 that showed immunological and reproductive effects of long-term low-level exposure of rats to radiofrequency (RF) electromagnetic fields. The early studies were used, in part, for developing exposure standards for the USSR population and thus it was necessary to confirm the Russian findings. In the present study, the conditions of RF exposure were made as similar as possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 3 publications
3
25
1
Order By: Relevance
“…The procedures previously adopted in Soviet Union and eastern countries utilized a large number of animals with lower ethical restrictions. In Soviet Union, experimental studies on longterm low level exposure of rats to radiofrequency EMFs, showed autoimmune and reproductive effects (21). These investigations were recently repeated showing the same general trend of the earlier studies evidencing that EMF exposure reduces the formation of antibodies in brain tissue with possible stimulation of autoimmune mechanisms; possible adverse effects on fetal development were also confirmed (21).…”
Section: Effects Of Electromagnetic Fields On the Immune Systemsupporting
confidence: 60%
“…The procedures previously adopted in Soviet Union and eastern countries utilized a large number of animals with lower ethical restrictions. In Soviet Union, experimental studies on longterm low level exposure of rats to radiofrequency EMFs, showed autoimmune and reproductive effects (21). These investigations were recently repeated showing the same general trend of the earlier studies evidencing that EMF exposure reduces the formation of antibodies in brain tissue with possible stimulation of autoimmune mechanisms; possible adverse effects on fetal development were also confirmed (21).…”
Section: Effects Of Electromagnetic Fields On the Immune Systemsupporting
confidence: 60%
“…The full results of both the French and Russian studies are given in Poulletier de Gannes et al [2009] and Grigoriev et al [2010] and only a brief summary is given to facilitate discussion.…”
Section: Resultsmentioning
confidence: 99%
“…This paper gives the IOC comments and conclusions on the differing results between the studies by Poulletier de Gannes et al [2009] and Grigoriev et al [2010].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…For the immune system [page 174 (2)], a Russian study was included (96), which mostly replicated earlier Russian studies and a French one which did not (97). The conclusion was "it is clear that the results of the original Soviet studies have not been confirmed".…”
Section: (C) Incorrect Statementsmentioning
confidence: 99%